1998
DOI: 10.1128/aem.64.8.2958-2965.1998
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of β-Subgroup Proteobacterial Ammonia Oxidizer Populations in Soil by Denaturing Gradient Gel Electrophoresis Analysis and Hierarchical Phylogenetic Probing

Abstract: A combination of denaturing gradient gel electrophoresis (DGGE) and oligonucleotide probing was used to investigate the influence of soil pH on the compositions of natural populations of autotrophic β-subgroup proteobacterial ammonia oxidizers. PCR primers specific to this group were used to amplify 16S ribosomal DNA (rDNA) from soils maintained for 36 years at a range of pH values, and PCR products were analyzed by DGGE. Genus- and cluster-specific probes were designed to bind to sequences within the region a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
144
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(163 citation statements)
references
References 30 publications
17
144
2
Order By: Relevance
“…Phylogenetic analysis showed that Nitrosospira cluster 3 dominated in soils, which is in agreement with previous study that Nitrosospira cluster 3 sequences were most common in agricultural fields (Kowalchuk et al, 2000). However, our result was inconsistent reports of selection of Nitrosospira cluster 2 in acidic soils (Stephen et al, 1996;1998;Kowalchuk et al, 2000). Given this discrepancy, additional sequence analysis was carried out for low pH treatments but no Nitrosospira cluster 2 sequence was found.…”
Section: Discussionsupporting
confidence: 87%
“…Phylogenetic analysis showed that Nitrosospira cluster 3 dominated in soils, which is in agreement with previous study that Nitrosospira cluster 3 sequences were most common in agricultural fields (Kowalchuk et al, 2000). However, our result was inconsistent reports of selection of Nitrosospira cluster 2 in acidic soils (Stephen et al, 1996;1998;Kowalchuk et al, 2000). Given this discrepancy, additional sequence analysis was carried out for low pH treatments but no Nitrosospira cluster 2 sequence was found.…”
Section: Discussionsupporting
confidence: 87%
“…In previous studies of this soil (e.g. Stephen et al, 1998), all sequences amplified by the bacterial ammonia oxidizer primers used here fell within recognized bacterial ammonia oxidizer phylogenetic groups. However, to determine identity of crenarchaeal DGGE bands, clone sequences (CBS16S1-6) representing the six dominant band positions in 16S rRNA gene DGGE profiles ( Fig.…”
Section: Phylogenetic Analysis Of Crenarchaeal 16s Rrna and Amoa Genementioning
confidence: 66%
“…However, it is important to note that even in the intensively managed system utilized by Bruns et al (1999), changes in qualitative phylogenetic diversity between native and cultivated soils are not always evident (Phillips et al 2000). Other studies suggest that AOB may be sensitive to the type of fertilizer application (Oved et al 2001), soil pH (Stephen et al 1998;Kowalchuk et al 2000), soil temperature (Avrahami et al 2003), and the heterogeneity of soil characteristics (Webster et al 2002), all of which can change differentially depending on management.…”
Section: Discussionmentioning
confidence: 99%